Life and freedom from the law of sin and death: A Hongkonger’s reflection - Sun, Poling (Review and expositor, 2021)
Since the Reformation, the significance of the death of Jesus has been understood as a soteriology that is personal and inward. This article suggests that, while the traditional-doctrinal articulations are important, Paul had his eyes on the Roman Empire, the propaganda and oppression of which were legitimized as law and constructed a world that was sinful and a means of death. The significance of Jesus’s death and, therefore, the gospel is more than “a gospel of sin management” but is an exposure of the sin of a power and a call to struggle for freedom through suffering. This article illustrates this reading with an account of recent developments in Hong Kong.